Analysis of the Use of Gastroprotectors in Patients with Stable and Unstable Angina Who Take Acetylsalytic Acid Preparations - Anvarovich, Djumayev Akbar (American Journal of Bioscience and Clinical Integrity, 2025)
Antithrombotic drugs (antiplatelet agents and anticoagulants) are widely used in cardiology practice for the first and second-degree prevention of thrombotic and thromboembolic complications. However, their use increases the risk of complications associated with bleeding, including gastrointestinal bleeding. The results of capsular videoendoscopy showed that antithrombotic drugs affect not only the upper part of the stomach, but also the lower parts - the small and large intestines. Therefore, in order to protect the mucous membrane of the gastrointestinal tract and prevent bleeding, it is advisable to use rebamide - a unique drug that combines gastro- and enteroprotective properties. Rebamypid acts on all structural levels of the mucous membrane throughout the gastrointestinal tract. Its effectiveness and safety have been proven in numerous randomized clinical trials.